2022
DOI: 10.1021/acs.chemrestox.1c00364
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria alternata Mycotoxins Activate the Aryl Hydrocarbon Receptor and Nrf2-ARE Pathway to Alter the Structure and Immune Response of Colon Epithelial Cells

Abstract: After ingestion of food commodities, the gastrointestinal tract (GIT) poses the first barrier against xenobiotics and pathogens. Therefore, it is regularly confronted with external stressors potentially affecting the inflammatory response and the epithelial barrier. Alternaria mycotoxins such as alternariol (AOH) and altertoxin II (ATX-II) are frequently occurring food and feed contaminants that are described for their immunomodulatory capacities. Hence, this study aimed at exploring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
3
6
0
Order By: Relevance
“…Morphological alterations in WI-38 and PCS-200-014 cells, such as irregular growth patterns and elongated arms, were observed after exposure to ALT, AOH, TeA, and AS for 24 h. These results are in line with those of Groestlinger et al [ 50 ], who reported that the binary mixture of Alternaria toxins AOH and altertoxin II (ATX-II) significantly altered the architecture of colon epithelial cells (HCEC-1CT) after 24 h of incubation. Similarly, ATX-II was also able to predominantly alter membrane functionality in intestinal epithelial cells (HCECs), thus hampering crucial functions for cellular motility [ 78 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Morphological alterations in WI-38 and PCS-200-014 cells, such as irregular growth patterns and elongated arms, were observed after exposure to ALT, AOH, TeA, and AS for 24 h. These results are in line with those of Groestlinger et al [ 50 ], who reported that the binary mixture of Alternaria toxins AOH and altertoxin II (ATX-II) significantly altered the architecture of colon epithelial cells (HCEC-1CT) after 24 h of incubation. Similarly, ATX-II was also able to predominantly alter membrane functionality in intestinal epithelial cells (HCECs), thus hampering crucial functions for cellular motility [ 78 ].…”
Section: Discussionsupporting
confidence: 90%
“…At the end of the experiment, samples from liver tissues were excised from the sacrificed animals of each group and preserved at −80 °C. The expressions of mRNAs for Tumor Necrosis Factor-α (TNF-α) gene were quantified using RT-PCR [ 50 ]. The total RNA was extracted from liver tissues (approximately 40 mg) using the RNAEasy kit (Qiagen, Germany), following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The decrease in total cellular NF-κB levels could, therefore, affect the transcription of cytokines responsible for the pro-inflammatory response. These results are similar to those found in Alternaria toxins, a family of sphinganine analogs, following treatment in the non-cancerous colon epithelial cell line HCEC-1CT [48]. It was shown that these toxins suppress the elevation of cytokine mRNA level relative to the inflammatory response and, therefore, the IL-8 secretion in a concentration-dependent manner starting at 1 µM AOH [48].…”
Section: Discussionsupporting
confidence: 84%
“…To preserve the staining until the imaging the slides were sealed and stored at 4 °C. For the staining of YAP1 protocol was slightly adapted and permeabilization was carried out as first step as previously described for other transcription factors (Groestlinger et al 2022 ). Images for Piezo1 and YAP1, actin, and nuclei were acquired with LSM Zeiss 710 equipped with ELYRA PS.1 system with a Plan Apochromat 63X/1.4 oil objective (zoom 1.5).…”
Section: Methodsmentioning
confidence: 99%